Uloga d-dimera u isključivanju plućne embolije u službi hitne medicinske pomoći - Maksimović, Žana M; Hadžić, Renata; Stajić, Mladen; Lončar-Stojiljković, Dragana (Scripta Medica, 2020)
Introduction. Pulmonary embolism (PE) is a diagnostic challenge, particularly in prehospital care. The aim of this study was to determine to what extent evaluation of D-dimer value helps physicians with differentiation of PE, and whether D-dimer values are in correlation with values of Revised Geneva Score. Methods. Data have been collected for the patients whose D-dimer has been evaluated at the Emergency Care Department of the City of Banja Luka in 2018. Gender, age, symptoms, working diagnosis and D-dimer value have all been recorded and also the fact whether the patient was referred to hospital treatment or not. For each patient the Revised Geneva Score was determined. Results. Sixty-eight tests have been done in 2018. Out of 68 tests, 41 were negative (60.3%). D-dimer results helped in making a decisions about referring patients to the hospital or not (χ2=36.32, p<0.001). Patients with elevated D-dimer levels, especially where the values were four times higher that the refence ones, typically were referred to hospital treatmant, whereas 67.5% patients with negative D-dimer results were sent home after giving treatment and advice. In the elderly patients D-dimer was statistically more positive (F=10.82, p<0.001). Values of D-dimer were not significantly different regarding gender (χ2=2.19, p=0.33). According to the results of the Revised Geneva Score, 5.1% of patients had high risk of PTE, while moderate and low risk had 47.5% each. Although it has been found that the values of D-dimer were slightly more elevated at higher values of the Revised Geneva Score, that difference was not statistically significant (χ2=7.71, p=0.10). Conclusion. Values of D-dimer considerably helped in diferentation of PE in the Emergency Care Department Banja Luka. D-dimer has a high negative predictive value and should be used to exclude PE diagnosis for patients with low clinical possibility of PE.